The impact of emerging Asia on commodity prices - Calista Cheung; Sylvie Morin (Bank of Canada, 2007)
Over the past 5 years, real energy and non-energy commodity prices have trended sharply higher. These relative price movements have had important implications for inflation and economic activity in both Canada and the rest of the world. China has accounted for the bulk of incremental demand for oil and many base metals over this period. As rapid economic growth in China has raised the level of world demand, this has put upward pressure on commodity prices. The effect has been amplified by rising resource intensities in China's production in recent years. This paper discusses the factors driving emerging Asia's demand for commodities and assesses the impact of emerging Asia on the real prices of oil and base metals in the Bank of Canada Commodity Price Index (BCPI). Two separate single-equation models are estimated for oil and the base metals price index. We employ a structural break approach for oil prices, while metals prices are modelled with an error correction model (ECM). In both cases, we find strong evidence that oil and metals prices have historically moved with the business cycle in the developed world, but that this relationship has broken down since mid-1997. Thereafter, industrial activity in emerging Asia appears to have become a more dominant driver of oil price movements. While metal price fluctuations have also become increasingly aligned with levels of industrial activity in emerging Asia, rising intensities of metal production may have been a more important factor behind the acceleration in prices in recent years.
Keywords: E3; F4; O19; Q11; 330; Business fluctuations and cycles; International topics; Rohstoffmarkt; Rohstoffpreis; Inflation; Wirtschaftswachstum; Fehlerkorrekturmodell; China; Kanada